INDEPENDENT LEARNING STRATEGY OF NATURAL SCIENCE WITH â€œONE DAY ONE DIARY FOR SCIENCEâ€ PROGRAM - Herlianti, P. S.; Linuwih, S.; Dwijananti, P. (Jurnal Pendidikan Fisika Indonesia, 2015)
Learning behavior and metacognitive skill of students affect cognitive value and level of understanding of each student. The application of the "One Day One Diary for Science" program is needed in learning to train students' metacognitive skills and independence in learning science. This study was performed to find out the learning behavior, the development of metacognitive skills, and both relation. The study was conducted by observation, interview, and documentation on 33 junior high school students. The result of the study was analyzed the domain, taxonomy, components, and culture growth, so the data of learning behavior and metacognitive skill of students based on the score level can be obtained. Based on data analysis, learning behavior and metacognitive skill on a higher grade is higher than the other classes. There is a strong correlation between learning behavior and metacognitive skills.Perilaku belajar dan kemampuan metakognitifÂ  siswa mempengaruhi nilai kognitif dan tingkat pemahaman setiap siswa. Penerapan programÂ  â€œ One Day One Diary for Scienceâ€ Â diperlukan dalam pembelajaran sains untuk melatih kemampuan metakognitif dan kemandirian siswa dalam belajar IPA. Penelitian ini bertujuan untuk mengetahui perilaku belajar, perkembangan kemampuan metakognitif, dan hubungan keduanya. Penelitian dilakukan dengan cara pengambilan data melalui Â pengamatan, wawancara, dan dokumentasi serta triangulasi data dengan cara memperpanjang lama pengamatan pada 33 siswa Sekolah Menengah Pertama. Hasil penelitian dianalisis dengan analisis domain, taksonomi, komponensial, dan temuan budaya, sehingga diperoleh data perilaku belajar sains Â dan kemampuan metakognitif siswa berdasarkan tingkatan kelas. Berdasarkan analisis data, perilaku belajar sains dan kemampuan metakogntif pada kelas atas lebih tinggi dibandingkan kelas lain. Terdapat hubungan yang kuat antara perilaku belajar dan kemampuan metakognitif